An activation-dependent, T-lymphocyte-specific transcriptional activator in the mouse mammary tumor virus env gene. - Miller, C L (1992)
Transcription of the complete mouse mammary tumor virus (MMTV) proviral genome in mouse cells is controlled by a strong promoter in its long terminal repeat. In the mouse T lymphoma EL4, there is a second, activation-dependent transcriptional initiation site within the envelope (env) gene, from which a short mRNA is generated, encoding the open reading frame of the long terminal repeat. We now report the isolation of a segment of the MMTV env gene (called META, for MMTV env transcriptional activator) which has the expected transcription-activating properties seen in EL4.E1 cells. Namely, it induces activation-dependent, T-lymphocyte-specific transcription of a chloramphenicol acetyltransferase reporter gene. It is active in mouse or human T-helper lymphocyte lines when they are stimulated to transcribe lymphokine genes but is inactive in unstimulated T-helper cells, fibroblasts, a cytotoxic T-lymphocyte line, and a mastocytoma cell line. Its activity is inhibited by cyclosporin A, a specific inhibitor of lymphokine transcription. Several forms of the META have been isolated from EL4.E1 cells, a mouse T-helper cell hybridoma, and from BALB/c spleen cells. Linked to the heterologous thymidine kinase promoter, a 400-bp portion of it is an inducible, orientation-independent, and cyclosporin A-sensitive transcriptional activator in T-helper cells.